From hydrophobic to hydrophilic polyvinylidenefluoride (PVDF) membranes by gaining new insight into material's properties. Issue 69 (29th July 2015) - Fontananova, E.; Bahattab, M. A.; Aljlil, S. A.; Alowairdy, M.; Rinaldi, G.; Vuono, D.; Nagy, J. B.; Drioli, E.; Di Profio, G.
<x xml:space="preserve">Abstract</x> From hydrophobic to hydrophilic PVDF membranes by a combination of functionalization by blending chemical additives and selection of manufacturing procedure.